2000
DOI: 10.1093/jn/130.11.2711
|View full text |Cite
|
Sign up to set email alerts
|

Food Stamps Are Associated with Food Security and Dietary Intake of Inner-City Preschoolers from Hartford, Connecticut

Abstract: The goal of the present study was to examine the association of the Food Stamp Program with the food security and dietary intake of low-income children from Hartford, CT, who were enrolled in the Supplemental Food Program for Women, Infants, and Children (WIC). We compared the food and nutrition situation of low-income preschoolers who received food stamps (FS, n = 59) with that of those who did not receive food stamps (NFS, n = 40). Children were an average age of 2.7 +/- 0.6 y, and 95% were receiving WIC ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 7 publications
3
20
0
2
Order By: Relevance
“…Degrees of food insecurity measured by the 10-item Radimer/Cornell Scale were linearly associated with socioeconomic status, representing the greater the food insecurity, the poorer the socioeconomic conditions. It suggests that a use of the scale was acceptable to assess food insecurity in Korea as in the cases of other countries (Kendall et al, 1996;Pérez-Escamilla et al, 2000;Studdert et al, 2001). Nevertheless, a direct validity test for Korean population seemed to be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Degrees of food insecurity measured by the 10-item Radimer/Cornell Scale were linearly associated with socioeconomic status, representing the greater the food insecurity, the poorer the socioeconomic conditions. It suggests that a use of the scale was acceptable to assess food insecurity in Korea as in the cases of other countries (Kendall et al, 1996;Pérez-Escamilla et al, 2000;Studdert et al, 2001). Nevertheless, a direct validity test for Korean population seemed to be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship suggests that management strategies might be an important area for intervention and education, as has been suggested for other low-income populations. For instance, Perez-Escamilla et al 15 showed in a communitybased study of low-income FSP participants in Hartford, Connecticut that early completion of food stamps was associated with increased likelihood of being food-insecure. Caseworkers at resettlement agencies have also reported that paying bills and managing money are among the primary difficulties experienced by newcomers to the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo realizado em Hartford, Estados Unidos, que comparou níveis de segurança alimentar em famílias beneficiárias ou não de programas assistenciais e contemplou famílias com crianças menores de sessenta meses, evidenciou que a inserção nos programas de suporte alimentar garantia a segurança alimentar e o consumo de micronutrientes pelas crianças 27 . No presente estudo, onde todas as famílias recebiam a cesta de alimentos e a maioria está inserida em programas de distribuição de renda, não foi observada a mesma relação, e o consumo adequado de micronutrientes também não foi constatado, seja para famílias beneficiárias ou não de programas de distribuição de renda.…”
Section: Discussionunclassified